2019
DOI: 10.3390/md17040242
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin as a Peroxisome Proliferator-Activated Receptor (PPAR) Modulator: Its Therapeutic Implications

Abstract: Peroxisome proliferator-activated receptors (PPARs) are part of the nuclear hormone receptors superfamily that plays a pivotal role in functions such as glucose and lipid homeostasis. Astaxanthin (ASX) is a lipid-soluble xanthophyll carotenoid synthesized by many microorganisms and various types of marine life that is known to possess antioxidant, anti-inflammatory, antidiabetic, anti-atherosclerotic, and anticancer activities. As such, it is a promising nutraceutical resource. ASX-mediated modulation of PPARs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 84 publications
(115 reference statements)
0
31
0
Order By: Relevance
“…AST offers a broad spectrum of other benefits to diabetic patients, including the suppression of inflammation and oxidative stress as well as the control of nonalcoholic fatty liver and diabetic complications [ 22 , 26 , 31 , 36 ]. AST functions as an antagonist of peroxisome proliferator-activated receptor (PPARγ) to exert its anti-inflammatory activity [ 37 ]. Our present study, focusing on the mechanisms of action of AST-mediated anti-hyperglycemic activity, has led to the identification of S6K1 as its molecular target.…”
Section: Discussionmentioning
confidence: 99%
“…AST offers a broad spectrum of other benefits to diabetic patients, including the suppression of inflammation and oxidative stress as well as the control of nonalcoholic fatty liver and diabetic complications [ 22 , 26 , 31 , 36 ]. AST functions as an antagonist of peroxisome proliferator-activated receptor (PPARγ) to exert its anti-inflammatory activity [ 37 ]. Our present study, focusing on the mechanisms of action of AST-mediated anti-hyperglycemic activity, has led to the identification of S6K1 as its molecular target.…”
Section: Discussionmentioning
confidence: 99%
“…Astaxanthin is the most common carotenoid in marine organisms, such as algae and aquatic animals. Previous studies indicated that astaxanthin has multiple pharmacological properties including antioxidant, anti-inflammatory, anti-cancer activities, and anti-adiposity action [22]. Therefore, adipose tissue mass represents an attractive concept for combating obesity and associated metabolic diseases [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has opposing effects on some PPARs, depending on the cell context. Regulation of PPARα and PPARγ activity by AX prevented hepatic injury by maintaining lipid homoeostasis, the cardio‐, neuro‐ and retino‐protective effects may be related to PPAR modulation (Choi, ).…”
Section: Astaxanthinmentioning
confidence: 99%
“…The underlying mechanisms for the effects of AX include its high antioxidant capacity, its role as a modulator of the peroxisome proliferator-activated receptors (PPAR; Choi, 2019) and its complex effects on signalling pathways associated with inflammation and apoptosis (see review by Fakhri et al, 2018). AX enhances the effect of the usual reservations about quality and independence of many nutraceutical studies, Andrew & Izzo, 2017).…”
Section: Mechanisms Of Actionmentioning
confidence: 99%